Tapeworms of dogs and cats in North America - Miller, Kamilyah R. (My University, 2025)
Dipylidium caninum and Echinococcus multilocularis are zoonotic tapeworms that infect domestic dogs and cats worldwide. Dipylidium caninum is transmitted by Ctenocephalides felis (the cat flea); recent reports show two host-adapted D. caninum strains, cat and dog, and resistance to praziquantel. Echinococcus multilocularis, transmitted by rodents, causes alveolar echinococcosis (AE) in domestic dogs and humans, and is a major public health concern in North America. This thesis addresses gaps in the prevalence of D. caninum in fleas and E. multilocularis in wild canids and the need to improve molecular diagnostics for E. multilocularis in domestic dogs and wild canids. In Chapter 2, our lab utilized a useful method for pool testing fleas for surveillance and assessing infection rate of D. caninum. This work demonstrated the prevalence of D. caninum in fleas of 3.8% through pool testing of fleas collected from the environment and on-animal. Molecular epidemiology also revealed the feline genotype of D. caninum was present in fleas collected from cats, matching D. caninum cat strains previously reported. In Chapter 3, our surveillance revealed that 47% of coyotes in Kansas and 42% in Missouri are infected with Echinococcus multilocularis, a new endemic region, plus a single red fox in Missouri. Additionally, 20% of coyotes in Illinois and 16% in Indiana were infected with E. multilocularis, which are known endemic regions. Molecular epidemiology revealed the European haplotype is present in wild canids in the Midwest United States, instead of the, previously reported, N2 North American haplotype. Thus, documents the expanding range of E. multilocularis and the highly pathogenic and zoonotic Europeans strains in North America. In Chapter 4, our work concluded that adult cestode recovery remains ‘the gold standard’ when compared to common diagnostic techniques such as fecal flotation, sedimentation and copro-PCR. I described the importance of developing a reliable method for extracting taeniid egg DNA for large scale surveillance of E. multilocularis in domestic dogs and wild canids. This thesis provides useful methods for surveillance of D. caninum in fleas through pool testing and data on the prevalence of Echinococcus multilocularis that can aid in the design of control and prevention programs.
Keywords: Echinococcus multilocularis; Coyote; Public health; Ctenocephalides felis; Diagnostics; Dipylidium caninum